PENENTUAN KADAR STPP FOOD GRADE UNTUK MENINGKATKAN MASA SIMPAN IKAN NILA TILAPIA (Oreochromis niloticus L.) - Leny Yuanita (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
The aim of the study was to determine Sodium Tripolyphosphate Food Grade (STPP FG) concentration as soaking solution at the safe limit to increase the quality and storage period of Nila tilapia (Oreochromis niloticus L). The first stage was to determine the combination of STPP FG concentration and the length time of soaking; the independent variables are STPP FG concentration, soaking time; the dependent variables are: P2O5 content, organoleptic parameter. The second stage was to determine the storage period; the independent variables are STPP FG concentration, soaking time, and storage period; while the dependent variables are chemical and microbiological quality. Data analysis were qualitative and quantitative descriptive. The results of the first stage study revealed that the variation of the STPP FG concentration and soaking time to meet the prerequirement of P2O5 content and the quality of Nila tilapia were: 90 g/l – 1 hour soaking time, 60 g/l – 2 hours soaking time, and 60 g/l – 1 hour soaking time. The second stage study showed that the storage period of Nila tilapia was 6 hours when variations of 90 g/l STPP FG concentration and 1 hours soaking time were applied; while variation of 60 g/l STPP FG - 2 hours soaking time and 60 g/l STPP FG - 1 hours soaking time were 4 and 2 hours storage period respectively.